Analisis Pemahaman Siklus Akuntansi Bagi Pemilik Usaha Laundry Di Kecamatan Ratu Agung Kota Bengkulu - Ina Sintia Wati; Tito Irwanto; Dewi Harwini (PT. MEMIKATTA PUBLISHER INDONESIA, 2024)
The purpose of this research is to understand how the owners of laundry businesses in Ratu Agung District, Bengkulu City, comprehend the accounting cycle in accordance with the principles of the correct accounting cycle. The data analysis in this study employs a qualitative analysis approach. The population for this research consists of all laundry businesses registered with the Cooperative and Small and Medium Enterprises Office of Bengkulu City in Ratu Agung District, with a sample of 19 respondents. The data collected in this study is primary data obtained directly from the respondents through observation, interviews, and questionnaires. The research findings indicate that the owners of laundry businesses in Ratu Agung District, Bengkulu City, have not implemented the accounting cycle according to the correct accounting principles. The calculation results from the distributed questionnaires show a weighted score of 25%, where the Guttman scale ranges from 0% to 25%, indicating no association or a low association (weak association). This means that the laundry business owners do not apply the accounting cycle, or the implementation of the accounting cycle is still very low/weak in their financial management. The application of the accounting cycle in laundry businesses is limited to the recording of transactions and transaction evidence. The lack of implementation of the accounting cycle among these owners is due to their belief that simply recording cash inflows and outflows is sufficient for their laundry business.